The second generation cryoballoon has improved durable isolation of left but not right pulmonary veins: new insights from a multicentre study. Issue 7 (12th July 2017) - Martins, Raphaël P; Galand, Vincent; Cesari, Olivier; Milhem, Antoine; Behar, Nathalie; Auffret, Vincent; Daubert, Jean-Claude; Mabo, Philippe; Pavin, Dominique
Abstract: Aims: Pulmonary vein isolation (PVI) using second-generation cryoballoon (CB2) is associated with improved outcomes compared with first generation (CB1). We aimed at investigating the characteristics of left and right PV reconnections after CB1 and CB2 ablations in patients with clinical recurrences requiring redo ablation. Methods and results: From 2010 to 2016, 776 patients underwent 28-mm cryoballoon PVI for symptomatic paroxysmal atrial fibrillation (AF) in 3 centres, 279 with CB1 and 497 with CB2. Among them, 94 patients (12.1%) had symptomatic AF recurrences requiring a redo ablation [43 (15.4%) CB1 and 51 (10.3%) CB2]. The benefit of CB2 over CB1 was compared for each PV. Durable PVI was confirmed in 7 CB1 (16.3%) and 14 CB2 (27.4%) patients, and 2.7 ± 2.1 and 1.4 ± 1.4 gaps per patient were found, respectively ( P = 0.002). Significantly more left superior and left inferior PVs were found to be isolated in CB2 compared with CB1 group (78.4% vs. 48.8%, P = 0.005 and 78.4% vs. 46.5%, P = 0.003, respectively) while the rate of durable right superior and right inferior PVs isolation were similar (68.6% vs. 60.5%, P = 0.542 and 66.7% vs. 55.8%, P = 0.387, respectively). Significantly fewer gaps were found in left PVs in CB2 patients, while there was no significant difference for right PVs. Gaps localization was similar in both groups. Conclusion: Fewer reconnection gaps are observed during redo ablations of paroxysmal AF in patients primarily ablated with CB2. This difference is driven by less reconnection gaps observed in both left PVs, while no difference was observed for right PVs.